Layanan Unit Minangkabau Corner di UPT. Perpustakaan Universitas Andalas - Putra, Rizki Rahmai; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
Based on the research results, we can conclude the following: First, there are facilities Coner Minangkabau books, literature, websites, and presents the writers . Second, obstacles encountered, namely: (1) the limitations of the collection, because Minangkabau Corner newly founded University of Andalas; (2) limited the HR (Human Resources), the views of librarians is limited; (3) rarely visited by pemustaka. Third, efforts are being made to overcome the obstacles, namely: (1) increase the number of collections, by looking into the various villages of Khazana keminangkabauan; (2) the addition of a professional librarian in order to improve the service system; (3) has a trick or appeal, so pemustaka continue to visit and read.Keyword: Service , Library , Minangkabau Corner .